Demographic profile of the intellectual disability nursing workforce in Australia: Findings from a national survey. Issue 3 (2nd July 2020) - Lewis, Peter; Collison, James; Whitehead, Lisa; Howie, Virginia; Feighan, Sarah; Wiese, Michele; O'Reilly, Kate; Jaques, Hayden; Wilson, Nathan J.
ABSTRACT: Background: Nurses provide technical and relational skills that are integral to the care of people with intellectual disability (ID) in Australia. However, little is known about the demographic profile of this section of the nursing workforce. Method: Administration of a survey to nurses whose primary role it is to care for people with ID nationwide Results: This brief report provides a description of the demographics of participants in the national survey. Of 101 participants, 78% were women and the mean age was 53.21 years. Participants held a variety of educational qualifications to prepare them for the care of people with ID. Conclusion: The findings suggest the need to consider the future unmet needs of people with ID given the ageing of this workforce. The ongoing support needs of people with ID depend upon the ongoing presence of nurses well prepared to meet the need of this group of people.